Wide distribution of Escherichia coli carrying IncF plasmids containing blaNDM-5 and rmtB resistance genes from hospitalized patients in England. Issue 8 (4th August 2022) - Turton, Jane F.; Pike, Rachel; Perry, Claire; Jenkins, Claire; Turton, Jack A.; Meunier, Danièle; Hopkins, Katie L
Abstract : Introduction . The New Delhi metallo-β-lactamase (NDM) variant NDM-5 was first described in 2011 in an isolate of Escherichia coli . We noted that a high proportion of isolates of E. coli positive for bla NDM carbapenemase genes submitted to the UK Health Security Agency (formerly Public Health England) between 2019 and mid-2021 carried the bla NDM-5 allele, with many co-harbouring rmtB, rendering them highly resistant to aminoglycosides as well as to most β-lactams. Hypothesis/Gap Statement . This observation suggested that a common plasmid may be circulating. Aim . To compare these isolates and describe the plasmids carrying these resistance elements. Methodology . All isolates were sequenced on an Illumina platform, with five also subjected to long-read nanopore sequencing to provide complete assemblies. The locations of bla NDM-5, rmtB and other associated genetic elements were identified. Susceptibility testing to a wide range of antibiotics was carried out on representative isolates. Results . The 34 isolates co-harbouring bla NDM-5 and rmtB were from 14 hospital groups and six different regions across England and consisted of 11 distinct sequence types. All carried IncF plasmids. Assembly of the NDM plasmids in five isolates revealed that they carried rmtB and bla NDM-5 in an IncF conjugative plasmid ranging in size from 85.5 to 161 kb. All carried a highly conserved region, previously described in E. coli plasmid pHC105-NDM, that included bla TEM-1B and rmtB followed by sequence bounded by two IS 26 elements containing ΔIS Aba125, bla NDM-5, ble, trpF and tat followed by IS CR1 and an integron with sul1, aadA2 and dfrA12 cassettes. This arrangement has been described in isolates from other countries and continents, suggesting that such plasmids are widely distributed, at least in E. coli, with similar plasmids also found in Klebsiella pneumoniae . Tested isolates were resistant to most antibiotics except colistin, fosfomycin and tigecycline. Conclusion . These observations suggest that conjugative plasmids carrying a highly conserved resistance gene segment have become widespread in England and elsewhere. This study highlights the value of routine whole-genome sequencing in identifying genetic elements responsible for resistance dissemination.